Estimation of airborne radon concentration inside historical Roman building at southeastern, Egypt. (2021) - Hanfi, M.Y.; Masoud, Masoud S.; Mostafa, Mostafa Y.A.
Abstract: Earth crust is the elementary source of radon gas. The presence of radioactive gases like radon and thoron in the surrounding environment is fundamentally due to the existence of these radionuclides or their parents in the soil, rocks, and building materials which are based on the earth's crust. So, it is needful to estimate these hazard radionuclides content in the ambient environments. The remnants of Roman buildings are located in in the Seila area, south-eastern, Egypt. A model masonry building is used to evaluate the indoor radon concentration. Airborne radon concentration was determined in a room with a volume dimension of 29.8 m 3 and a surface area of 49.6 m 2, with an air exchange rate of 1 h −1 . The detection of uranium contents in the building materials of the roman house using a handled spectrometer RS-230. The estimated radon flux density JDb is 2 ± 0.46 mBqm −2 s −1 . The indoor radon concentration-related radon flux density was estimated at 20 Bqm −3 . This value is lower than the worldwide average of 40 Bqm −3 with indoor annual effective dose ERn, indoor (mSv) 0.6 mSv. This value is also lower than the worldwide effective dose of 1 mSv according to UNSCEAR.